Lavender Aromatherapy and Deep Breathing Relaxation on Reducing The Anxiety of Cancer Patients - Syahida, Ilma Yosi; Astuti, Duwi Pudji; Tarnoto, Koko Wahyu; Sulistyowati, Dwi Ariani (Universitas Muhammadiyah Semarang, 2024)
Cancer is a disease with an abnormal spread of uncontrolled body tissue cells and attacks adjacent body parts. One of the nursing problems that arise in cancer patients in anxiety. This study aims to determine the effect of lavender aromatherapy and deep breathing relaxation against depression and anxiety levels of cancer patients. This study applied a pre-experimental with one group pretest posttest design with a sample size of 36 respondents. The results showed and impact of lavender aromatherapy and deep breathing relaxation on reducing the anxiety of cancer patients, with a p-value of 0,000, and there is a significant difference in reducing the anxiety level of cancer patients before and after being given the intervention. Cancer patient with anxiety problem. It is recommended to use levender aromatherapy and deep breathing relaxation to relieve their symptoms.